Modern approaches to drug therapy of bladder cancer after first progression. - L. V. Bolotina; L. A. Koroleva (Исследования и практика в медицине)
The number of drugs that is effective in urothelial cancer is very little. Cisplatin remains the basic drug for first line, but its use may be limited because of significant toxic reactions, that develop in a great number of patients. In case of impossibility of use of platinum derivatives treatment may be limited to the use of gemcitabine as monotherapy. It is much more difficult to resolve the issue regarding patients progressing after 1st line treatment. The effectiveness of ifosfamide, taxanes, topotecan, epitilon B, pemetrexed, nab-paclitaxel, pralatrexate, targeted drugs or their combinations had not lived up to expectations. Vinflunine (Javlor) is the innovative chemotherapeutic drug that is effective for the treatment of platinum-refractory urotelial cancer, including a phase-3 trial. We have our own positive experience with Javlor in older age group of patients, that is presented in the article